A new European species of Pegomya Robineau-Desvoidy (Diptera: Anthomyiidae) near P. flavoscutellata (Zetterstedt) - Michelsen, Verner (Zootaxa, 2006)
A new species of Pegomya Robineau-Desvoidy is described from Europe (Sweden, Denmark and Finland) by the name of P. curviphallis. It belongs, together with the Holarctic P. flavoscutellata (Zetterstedt) and the Nearctic P. flaviantennata Griffiths, in a species group defined by a sickle-shaped distiphallus. Differential descriptions are given for the two European species of the P. flavoscutellata species group, P. curviphallis sp. nov. and P. flavoscutellata. Larvae of P. flavoscutellata are known to feed on bolete mushrooms (Leccinum spp.), and a similar larval diet can be expected in other species of the P. flavoscutellata species group.